1999
DOI: 10.1080/01616412.1999.11740944
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring spinal cord motor and somatosensory evoked potentials in anesthetized primates

Abstract: Monitoring Motor Evoked Potential (MEP) to Transcranial Stimulation (TMS) monitoring (MEP) is a growing technique to assess motor function under anesthesia. The following primate study was conducted to analyze the non-myogenic spinal motor and sensory volleys and to examine their reproducibility under nitrous oxide-methohexidone anesthesia. The traveling periodic spinal descending MEP to TMS and ascending somatosensory (SEP) to posterior tibial nerve stimulation across the thoracic cord were recorded in 12 cyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…1994). In primates, a N 2 O‐methohexital anaesthesia had little effect on the transmission of motor and sensory potentials (Ghaly et al . 1999), but isofluorane had a depressive action on spinal motor potentials (Baker et al .…”
Section: Discussionmentioning
confidence: 99%
“…1994). In primates, a N 2 O‐methohexital anaesthesia had little effect on the transmission of motor and sensory potentials (Ghaly et al . 1999), but isofluorane had a depressive action on spinal motor potentials (Baker et al .…”
Section: Discussionmentioning
confidence: 99%
“…A third explanation could be the influence of the strength of stimulation. Previous studies in cats and primates have demonstrated that the MMEP evoked by nearthreshold stimulation of the motor cortex consists of a series of waves generated in the motor cortex and conducted along the corticospinal tract (Haghighi et al 1995;Hiraizumi et al 1996;Ghaly et al 1999). However, Konrad and Tacker (1990) found that suprathreshold stimulation of the motor cortex in cats produced large MMEPs which travelled in the ventral funiculus and, therefore, were probably associated with extrapyramidal tracts, such as the reticulospinal and vestibulospinal tracts.…”
Section: Discussionmentioning
confidence: 99%